Species richness and asynchrony maintain the stability of primary productivity against seasonal climatic variability - Zhang, Ze; Hautier, Yann; Bao, Tiejun; Yang, Jie; Qing, Hua; Liu, Zhongling; Wang, Min; Li, Taoke; Yan, Mei; Zhang, Guanglin (Frontiers in Plant Science, 2022)
The stability of grassland communities informs us about the ability of grasslands to provide reliable services despite environmental fluctuations. There is large evidence that higher plant diversity and asynchrony among species stabilizes grassland primary productivity against interannual climate variability. Whether biodiversity and asynchrony among species and functional groups stabilize grassland productivity against seasonal climate variability remains unknown. Here, using 29-year monitoring of a temperate grassland, we found lower community temporal stability with higher seasonal climate variability (temperature and precipitation). This was due to a combination of processes including related species richness, species asynchrony, functional group asynchrony and dominant species stability. Among those processes, functional group asynchrony had the strongest contribution to community compensatory dynamics and community stability. Based on a long-term study spanning 29 years, our results indicate that biodiversity and compensatory dynamics a key for the stable provision of grassland function against increasing seasonal climate variability.